Near‐Ultraviolet to Near‐Infrared Spectral Properties of Hollows on Mercury: Implications for Origin and Formation Process. Issue 12 (17th December 2020) - Barraud, O.; Doressoundiram, A.; Besse, S.; Sunshine, J. M.
Abstract: Among the geological features revealed by the MESSENGER (MErcury Surface, Space ENvironment, GEochemistry and Ranging) mission on the surface of Mercury, hollows are the most surprising and least understood. Possibly related to volatile components, hollows are small depressions, surrounded by bright halos and are not observed on any other surfaces in our solar system. Previous analysis of multispectral data obtained by Mercury Dual Imaging System (MDIS) has shown that some hollows have weak spectral absorption features centered at around 600 nm. In this work, we analyzed four hollows with observations acquired by the Mercury Atmospheric and Surface Composition Spectrometer (MASCS) on board MESSENGER with more than 230 spectral channels from the near‐ultraviolet to the near‐infrared. Unlike previous MDIS multispectral data, the MASCS reflectance spectra exhibit no absorption features in the MDIS wavelength range. However, we found that hollows have unique spectral properties in the near‐ultraviolet, with a spectral curvature between 300 and 600 nm that is distinctly different from other geological units. Moreover, we used MASCS observations with the best available spatial resolution (<0.5 km/pixel) to analyze both parts of a hollow: the flat floor and the surrounding halo. Our results support the hypothesis that hollows form by a sublimation process and scarp retreat. Plain Language Summary: The MESSENGER (MErcury Surface, Space ENvironment, GEochemistry and Ranging) mission highlighted several geological terrains on Mercury's surface. Among the unexpected discoveries are small bright depressions, named hollows. Often found within impact craters, hollows have irregular shapes, flat floors, and are surrounded by bright halos. Hollows are still poorly understood and their formation remains a mystery for the scientific community. Using observations made by the spectrometer onboard the MESSENGER probe, we show for the first time that the spectra of hollows exhibit unique reflectance properties at near‐ultraviolet to visible wavelengths, which spectrally distinguishes them from other geological terrains. Moreover, the most detailed observations show that their flat floors have different spectral characteristics from the bright halos. Our results provide new knowledge about their formation, nature, and differences from other geological terrains and is consistent with them forming from sublimation processes. Key Points: Hollows have unique spectral properties in the near‐ultraviolet The reflectance spectra of hollows have a pronounced curvature between 300 and 600 nm Eminescu impact crater hollows are seen to grow via scarp retreat